Mixed convective flow of unsteady hydromagnetic couple stress fluid through a vertical channel filled with porous medium - Makhalemele, Cynthia; Rundora, Lazarus; Adesanya, Samuel Olumide (Zielona Góra: Uniwersytet Zielonogórski)
In this paper, the mixed convective flow of an electrically conducting, viscous incompressible couple stress fluid through a vertical channel filled with a saturated porous medium has been investigated. The fluid is assumed to be driven by both buoyancy force and oscillatory pressure gradient parallel to the channel plates. A uniform magnetic field of strength B0 is imposed transverse to the channel boundaries.
Keywords: couple stress fluid; mixed convection; magnetohydrodynamics; oscillatory flow